PCR fingerprinting of Blastocystis isolated from symptomatic and asymptomatic human hosts - Tan, Tian Chye; Suresh, K.G.; Thong, Kwai Lin; Smith, H.V. (Springer Verlag (Germany), 2006)
Genomic DNA from 16 Blastocystis hominis isolates comprising of eight asymptomatic isolates (A1-A8) and eight symptomatic isolates (S1-S8) was amplified by arbitrarily primed polymerase chain reaction (AP-PCR) using 38 arbitrary 10-mer primers. Six primers (A10, B5, C20, D1, F6, and F10) generated reproducible DNA fingerprints. AP-PCR amplification revealed similar DNA fingerprints among all symptomatic isolates (S1-S8) with common bands at 850 bp using primer A10, 920 bp using primer B5, and 1.3 kbp using primer D1. Isolates A1, A3, A4, A5, A6, and A7 showed similar DNA banding patterns and all asymptomatic isolates (A1-A8) shared a major band at I kbp using primer B5. Isolates A2 and A8 showed distinct DNA banding patterns that differed from the remainder of the isolates. The results of the phylogenetic analyses showed that all symptomatic isolates (S1-S8) formed, a clade with > 70 similarity among the isolates and which were clearly separate from asymptomatic isolates A1, A3, A4, A5, A6, and AT Asymptomatic isolates A2 and A8 formed two distinct and separate clades. AP-PCR revealed higher genetic variability within the asymptomatic isolates than within the symptomatic isolates. The present study suggests that AP-PCR can be a valuable method for differentiating between isolates of B. hominis and our results support the hypothesis that our asymptomatic and symptomatic B. hominis isolates may represent two different strains/species with varying pathogenic potential.